Cross-species comparison of rodent and human decision-making in the Iowa Gambling Task in select neurological and psychiatric disorders: translational approach to examine age- and sex-specific effects of stress and corticolimbic perturbations - Varsha Singh; Manjari Tripathi; Sarat P. Chandra; Rohit Verma; Sushil Kumar Jha; Harvinder Singh Chhabra; Mrinmoy Chakravarty; Mrinmoy Chakravarty; Shambhovi Mitra; Indupriya B; Ankit Jha; Sakshi Sharma; et al. (Frontiers in Psychiatry)
IntroductionRodent models are widely used to understand brain pathologies and address cognitive deficits experienced by humans diagnosed with clinical disorders. However, stark differences in the nervous system and in the environmental demands of rodents and humans make it difficult to translate insights from rodents to humans. Age and sex further increase vulnerability to disorders via experiences marked by neglect, deprivation, threat, and constraining environments instead of care, nutrition, safety, and enriching environment. These differences impact cognitive processing of rewards, risks, and decision-making. Although rodent models allow for investigations of precise brain regions critical for decision-making, such as the prefrontal cortex (PFC), and enable controlled exposure to stress and disorder trajectories, the prefrontal cortex of rodents and humans differ in size, cytoarchitecture, and anatomical–functional organization. This non-analogous structural–functional mapping of brain regions and cognitive deficits result in rodent models that fail to establish causal links of brain pathophysiology and clinical conditions, and the model remains a poor depiction of cognitive deficits experienced by humans. We argue that the Iowa Gambling Task (IGT) is characterized by molecules to behavior, relies on intact cognitive, affective, and motivational systems of inhibitive control involving cortico-limbic circuitry in both humans and rodents.MethodWe conducted a rodent–human task comparison under stress and disruption in the central nervous system (CNS) to link cognitive deficits in poor decision-making with disruptions in brain architecture. A cross-species comparison, accounting for age and sex, was performed on pooled data from human and rodent IGT studies (N = 892; humans = 722; rodents = 170) to examine organism-, age-, and sex-specific decision-making under three levels of stress—psychological stress, CNS perturbation, and limbic perturbation—that can impair decision-making.ResultsThe results from four mixed-factor analyses of variances corrected for multiple group comparison showed that stress, CNS perturbation, and limbic perturbations impaired decision making. The adverse effects of psychological stress and CNS perturbations were unique to human task performance, while the adverse effect of limbic perturbations was age-specific in humans and sex-specific in rodents. Infrequent punishment choice was prominent in humans (women), and the healthy group compared to rodents (males) and the CNS perturbed group.DiscussionFindings suggest that the task might be useful for producing reliable cross-species comparisons of causal mechanisms underlying cognitive deficits in clinical disorders. Preclinical and clinical studies could use the task to reduce the translational gap in neurobiological and clinical neuroscience in ways that might be useful in improving human health.